Combinatorial Summation!

Calculus Level 5

n = 0 2 n + 1 ( 2 n + 1 ) ( 2 n n ) \large{ \sum_{n=0}^{\infty} \dfrac{2^{n+1}}{(2n+1) \ {2n \choose n} }}

If the summation above can be represented as A π B \large{A \cdot \pi^B} , where A , B A,B are positive integers, then find the value of ( A + B ) 3 (A+B)^3 ?


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Satyajit Mohanty
Jul 24, 2015

Therefore, we have A = 1 , B = 1 , A + B = 2 , ( A + B ) 3 = 8 A=1, B=1, A+B =2, (A+B)^3 = \boxed{8} .

Moderator note:

Is there a reason why you chose the power series of ( arcsin ( x ) ) 2 (\arcsin(x) )^2 ?

@ChallengeMaster : Because, I thought of this problem while I was studying Power series of ( arcsin ( x ) ) 2 (\arcsin(x))^2 .

Satyajit Mohanty - 5 years, 10 months ago
Sudeep Salgia
Jul 25, 2015

S = n = 0 2 n + 1 ( 2 n + 1 ) ( 2 n n ) = n = 0 1 2 n 1 . 2 2 n ( n ! ) 2 ( 2 n + 1 ) ! \displaystyle S =\sum_{n=0}^{\infty } \frac{2^{n+1}}{(2n+1) \binom{2n}{n} } = \sum_{n=0}^{\infty } \frac{1}{2^{n-1}} . \frac{2^{2n} ( n!)^2 }{ (2n+1)!}

Using the fact that 0 π 2 sin m x d x = 2 2 n ( n ! ) 2 ( 2 n + 1 ) ! \displaystyle \int_0^{ \frac{ \pi}{2} } \sin ^m x \text{ d}x = \frac{2^{2n} ( n!)^2 }{ (2n+1)!} for m = 2 n + 1 m = 2n +1 (Refer Wallis' Integrals ), we can write S S as ,

S = n = 0 1 2 n 1 . 0 π 2 sin 2 n + 1 x d x \displaystyle S = \sum_{n=0}^{\infty } \frac{1}{2^{n-1}} . \int_0^{ \frac{ \pi}{2} } \sin ^{2n+1} x \text{ d}x

S = 0 π 2 2 sin x ( n = 0 ( sin 2 x 2 ) n ) d x = 0 π 2 2 sin x . 1 1 sin 2 x 2 d x = 0 π 2 4 sin x 2 sin 2 x d x = 0 π 2 4 sin x 1 + cos 2 x d x \displaystyle \begin{array}{c}\\ S && = \int_0^{ \frac{ \pi}{2} } 2 \sin x \left( \sum_{n=0}^{\infty } \left( \frac{\sin ^{2} x}{2} \right)^n \right) \text{ d}x \\ && = \int_0^{ \frac{ \pi}{2} } 2 \sin x . \frac{1}{1 - \frac{\sin ^{2} x}{2} } \text{ d}x \\ && = \int_0^{ \frac{ \pi}{2} } \frac{ 4 \sin x }{ 2 - \sin ^2 x } \text{ d}x \\ && = \int_0^{ \frac{ \pi}{2} } \frac{ 4 \sin x }{ 1 + \cos ^2 x } \text{ d}x \\ \end{array}

Substitute u = cos x d u = sin x d x u = \cos x \Rightarrow \text{ d}u = -\sin x \text{ d}x in the integral to obtain,
S = 1 0 4 1 + u 2 d u = ( 4 ) . ( π 4 ) = π \displaystyle S = - \int_1^0 \frac{4}{1 + u^2} \text{ d}u = (-4). \left( -\frac{\pi }{4} \right) = \pi .

Compare the coefficients to evaluate the required value to get the answer as 8 \displaystyle \boxed{8} .

Moderator note:

Good observation with Wallis integral, which allows us to convert it into a geometric progression.

How did you solve the series n = 0 ( sin 2 ( x ) 2 ) n \sum_{n=0}^\infty(\frac{\sin^2(x)}{2})^n ? I am not an expert in math,still learning...

Timothy Wan - 5 years, 10 months ago

Log in to reply

It is an infinite geometric progression with ratio r < 1 |r| < 1 . Check the wiki - Geometric Progression for more information.

Satyajit Mohanty - 5 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...